Adaptive and plastic responses of Quercus petraea populations to climate across Europe. (25th January 2017) - Sáenz‐Romero, Cuauhtémoc; Lamy, Jean‐Baptiste; Ducousso, Alexis; Musch, Brigitte; Ehrenmann, François; Delzon, Sylvain; Cavers, Stephen; Chałupka, Władysław; Dağdaş, Said; Hansen, Jon Kehlet; Lee, Steve J.; Liesebach, Mirko; et al.
Abstract: How temperate forests will respond to climate change is uncertain; projections range from severe decline to increased growth. We conducted field tests of sessile oak ( Quercus petraea), a widespread keystone European forest tree species, including more than 150 000 trees sourced from 116 geographically diverse populations. The tests were planted on 23 field sites in six European countries, in order to expose them to a wide range of climates, including sites reflecting future warmer and drier climates. By assessing tree height and survival, our objectives were twofold: (i) to identify the source of differential population responses to climate (genetic differentiation due to past divergent climatic selection vs. plastic responses to ongoing climate change) and (ii) to explore which climatic variables (temperature or precipitation) trigger the population responses. Tree growth and survival were modeled for contemporary climate and then projected using data from four regional climate models for years 2071–2100, using two greenhouse gas concentration trajectory scenarios each. Overall, results indicated a moderate response of tree height and survival to climate variation, with changes in dryness (either annual or during the growing season) explaining the major part of the response. While, on average, populations exhibited local adaptation, there was significant clinal population differentiation for height growth with winter temperature at the site of origin. The most moderate climate model (HIRHAM5‐EC; rcp4.5) predicted minor decreases in height and survival, while the most extreme model (CCLM4‐GEM2‐ES; rcp8.5) predicted large decreases in survival and growth for southern and southeastern edge populations (Hungary and Turkey). Other nonmarginal populations with continental climates were predicted to be severely and negatively affected (Bercé, France), while populations at the contemporary northern limit (colder and humid maritime regions; Denmark and Norway) will probably not show large changes in growth and survival in response to climate change. Abstract : We conducted field experiments where more than 150 000 trees from 116 geographically diverse populations of sessile oak were planted on 23 field sites in six European countries. Population responses for tree growth and survival were modeled for contemporary climate and then projected using data from four regional climate models for years 2071–2100. Overall, results indicated a moderate response of sessile oak to climate variation, with changes in dryness explaining a predominant part of the response. Stronger and more negative future responses are expected for southeastern populations (Turkey, Hungary) than for central and northern populations (Denmark, Norway).